Mindfulness as a predictor of impulsive behavior among female high school students in Jeddah, Saudi Arabia - Alharbi, Nojod Melfi (Journal of Educational and Psychological Sciences, 2025)
The study aimed to examine mindfulness as a predictor of impulsive behavior among female secondary school students in Jeddah, Saudi Arabia. The study followed a descriptive-analytical approach. The study sample consisted of (85) female secondary school students. The results showed that the level of mindfulness dimensions (observation, description, acting consciously, and non-judgment) was moderate. The level of impulsive behavior dimensions (positive urgency, negative urgency, weak insight, lack of perseverance, and pursuit of feeling) was high. There is a negative relationship between all dimensions of mindfulness and their total score and all dimensions of impulsive behavior and their total score. Impulsive behavior can be predicted through the dimensions of mindfulness. The study’s most prominent recommendations included the need to provide programs to raise awareness among female secondary school students about the seriousness of impulsive behavior, hold training courses to develop mindfulness, and encourage researchers to conduct further studies and research on impulsive behavior to explore its relationship with other variables.